Reformas al art. 134 de la Ley de Minería regulando la minería artesanal - Sanchez Reyes, Jose Alberto (2016)
The Article 134 of the Mining Act stipulates that thatto artisanal mining is considered no more than one hundred and fifty unified basic salary, which gives the amount of forty-seven thousand seven hundred and associated investment and if three or more investment should not exceed ninety-five thousand four hundred dollars. These amounts appear exaggerated because artisanal mining may not be handmade with such amounts of investment as no artisanal mining has so much money, that allows miners to masquerade as artisanal miners to get these benefits without really craft but large mining. As noted in my thesis substantiate and demonstrated to be reformed Article 134 of the Mining Act by modifying the amount of investment to be considered as artisanal miners